Inequality in carbon intensity in EU-28: analysis based on club convergence - Emir, Firat; Balcilar, Mehmet; Shahbaz, Muhammad (Springer Heidelberg, 2019)
This study examines the convergence properties of CO2 intensity in EU-28 countries, using panel data for the period 1990 to 2016. We use Phillips and Sul's (2007) approach to test for CO2 intensity convergence and identify convergence clubs. In addition to the EU-28 members, we analyze the EU-15, and the new EU members (EU-new) that joined after 2004, as distinct groups for the periods 1990-2016, 1990-2004, and 2005-2016. Our results show no convergence to a single group among the EU countries during the full and two subsample periods. However, the convergence takes place within five to seven clubs for the EU-28 and within three to five clubs for the EU-15 and EU-new. There is no evidence of all members converging to a single club in either group or the three sub-periods examined. This study highlights the need for adopting new strategies considering club properties and for sustainable growth, which meets the EU-28 environmental regulation standards.
Keywords: Carbon intensity; Club convergence; Convergence test; European Union